FEMINISME ISLAM DALAM TEKS, KONTEKS, SERTA BUDAYA: PENDEKATAN KOMPARATIF DALAM PERSPEKTIF TAFSIR KLASIK DAN KONTEMPORER - Lukman Nul Hakim; Meliza; Ririn; Abdul Rouf (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine Islamic feminism in the dimensions of text, context, and culture through a comparative approach between classical and contemporary Qur’anic interpretations. Islamic feminism is understood as an effort to affirm principles of justice and gender equality rooted in the Qur’an and Sunnah, yet often influenced by socio-cultural and patriarchal constructions in interpretative practices. This research employs a qualitative method using a library research approach, combined with comparative analysis of Qur’anic interpretations related to women and gender relations. Primary data are derived from classical and contemporary tafsir works, while secondary data are obtained from relevant books and scholarly articles on Islamic feminism. The findings reveal that classical tafsir tends to emphasize a normative-textual approach shaped by its historical and social context, whereas contemporary tafsir adopts a more contextual approach that prioritizes substantive justice and ethical values. These differences do not indicate a contradiction in fundamental principles, but rather reflect methodological diversity in interpreting sacred texts. This study concludes that Islamic feminism represents an integral part of Islamic intellectual discourse that seeks to address modern social challenges while remaining grounded in Qur’anic normative foundations.